YEATS domain-containing 2 (YEATS2), targeted by microRNA miR-378a-5p, regulates growth and metastasis in head and neck squamous cell carcinoma. Issue 1 (1st January 2021) - Sha, Tong; Li, Jia; Sun, Shiqun; Li, Jianing; Zhao, Xuetao; Li, Zehua; Cui, Zhi
ABSTRACT: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide with poor prognosis and the development of HNSCC is a complex process. Some research have found that YEATS domain-containing 2 (YEATS2) is highly expressed in non-small cell lung cancer and pancreatic cancer, whereas its function in HNSCC is left to be studied. The primary aim was to investigate the role of YEATS2 in proliferation, apoptosis, invasion and migration in HNSCC cells and explore the possible mechanisms. We found YEATS2 expression was elevated in HNSCC clinical samples. Our work also indicated YEATS2 knockdown inhibited cell proliferation, induced apoptosis, and diminished the migration and invasion capability in HNSCC cell lines, including Detroit562 and FaDu cells. Besides, these inhibiting effects of YEATS2 knockdown could be crippled by microRNA-378a-5p (miR-378a-5p) inhibitor. In conclusion, our data suggested that YEATS2 expression was regulated by miR-378a-5p and YEATS2 knockdown inhibited proliferation and metastasis while induced apoptosis in HNSCC cells.